(3fXQjI GdeDGeQI hGdEfgjGQ GdeUQaj Hjf caGjI ebQQGJ dLfI HGRd hJbdjd GdeNGWQ GdeUQajI (B:s (3OQGSI JMdjdjI GSJWdGYjI (B/s - (3NejS, YHO GdSdGe eMeOs; (3GdYRGhj, eMeO YHO GdhgGH s ((3HZOGO(B: s (3GdPGcQI ddfTQ hGdJhRjY(B, s, 2014)
(3jVe fXQjI GdeDGeQI hGdCReI GdeGdjI, ebQQGJ HGRd hGdQbGHI GdeUQajI, GdOQGSGJ GdNGUI HGdQbGHI GdeUQajI, EOGQI GdeNGWQ GdeGdjI, GdOQGSGJ GdNGUI HGdeNGWQ hGdESJbQGQ GdeGdj, GdJMdjd GdeGdj ddeUGQa GdGeQjcjI, caGjI QCS GdeGd hQbGHI Hfc GdEMJjGW GdajOQGdj, JOGYjGJ GdCReI hGdOQhS GdeSJaGOI, fXQjI GdeDGeQI hGdQDi GdeSJbHdjIs
(3GdeUGOQ U(B.210s
Keywords: (3GdCReGJ GdEbJUGOjIs; (3GdQbGHI GdeUQajIs; (3GdeNGWQ GdeGdjIs